2013
DOI: 10.1111/1440-1681.12106
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role for ambulatory blood pressure monitoring in pregnancy?

Abstract: 1. Ambulatory blood pressure monitoring (ABPM) has been used in pregnancy for just over 20 years now and is generally well tolerated. Normal values have been established for different gestations; these are slightly higher than conventional blood pressure (BP) in normal pregnancy, presumably reflecting greater activity during the 24 h of ABPM recordings. 2. Ambulatory blood pressure monitoring is a better predictor than conventional BP for the development of pre-eclampsia and fetal growth restriction, but it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 43 publications
1
30
1
1
Order By: Relevance
“…3,4,35 In the present study, ABPM was very useful for detecting WCH even in patients suspected of PE or GH. 36 This is true not only in the early phase of pregnancy, 36 but also the late phase as shown in the present study. Because the pregnancy outcome is favorable in women with WCH, diagnosing WCH by ABPM is helpful to avoid early and unnecessary termination of pregnancy for hypertensive women.…”
Section: Discussionsupporting
confidence: 78%
“…3,4,35 In the present study, ABPM was very useful for detecting WCH even in patients suspected of PE or GH. 36 This is true not only in the early phase of pregnancy, 36 but also the late phase as shown in the present study. Because the pregnancy outcome is favorable in women with WCH, diagnosing WCH by ABPM is helpful to avoid early and unnecessary termination of pregnancy for hypertensive women.…”
Section: Discussionsupporting
confidence: 78%
“…Despite that, a small proportion of patients with WCH in early pregnancy will develop PE later in pregnancy. 89,90 Consequently, it is essential to differentiate WCH from PIH, thus avoiding exposing these women to the possible adverse effects of antihypertensive treatment as well as unnecessary caesarean sections. In addition, detection of that group of women with WCH who are going to develop PE is important for pregnancy outcome.…”
Section: Follow-upmentioning
confidence: 99%
“…4.1). If out-of-office BP readings cannot be obtained, it is recommended to confirm the HT diagnosis using repeated office measurements, preferably taken by a nurse [16,17].…”
Section: Treatment Of Ht In Women At Reproductive Agementioning
confidence: 99%
“…The number of studies assessing out-of-office BP values in pregnancy is limited. Informed by the results of studies published to date, some recommendations consider readings slightly lower than in the general population (mean daytime BP ≥ 130/80 mm Hg and mean nocturnal BP ≥ 110/70 mm Hg) as the threshold for HT diagnosis in 24-hour BP recording [1,16]. However, we concluded that in the absence of data unequivocally indicating the prognostic significance and in order to avoid overtreatment in pregnancy, the same threshold BP values which are used in the general population should apply [4]…”
Section: Diagnosis Of Ht In Pregnancymentioning
confidence: 99%